(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
In the defined teaching unit of athletics the study draws attention to the importance and possibility of differentiation in individualized education and assessment relating to the students’ diversity. The elaborated method based on pulse measurement supports group formation and differentiation objectively in the light of various abilities and physical conditions. Group formation was applied for the students with dissimilar load ability to reach uniform intensity during the lesson. Intensity was determined for which the groups included students with differing abilities receiving different tasks eliminating the possibility of being over and under loaded. The research demonstrates the efficiency of this method. The direct aim of the measurement is that the objective evaluation and predictability of Physical Education should get proven. In the future the new method gives a comprehensive picture about the tested student’s load ability, endurance (individualized) as well as it makes the students’ assessment easier.